Analysis of Residual Soil Properties on Slope: A Study in Dusun, Universiti Teknologi Malaysia, Johor - Norhidayah Mohamed; Muhammad Farhan Zolkepli; Ahmad Safuan A. Rashid; Azman Kassim; Muhammad Syamsul Imran Zaini; Muhammad Irfan Shahrin; Mohd Fakhrurrazi Ishak; Zaihasra Abu Talib (International Journal of Integrated Engineering, 2024)
The actual characterization of residual soil differs across different countries. Any soil that has remained at its original location without being moved is commonly referred to as residual soil. In order to build geotechnical infrastructures that are safe and cost-effective, it is essential to have a thorough understanding of the properties of residual soil, which includes slope stability. This knowledge offers valuable insights into the characteristics and strength of the soil. Slope failure is a widespread and devastating disaster that can occur in various regions, including Malaysia. Given the numerous incidents caused by slope failure, it is vital to conduct a thorough scientific study to determine the specific soil characteristics at Dusun UTM, Johor. Numerous laboratory studies have been carried out regarding the soil’s index of physical as well as engineering properties. The area can be characterized as having sandy silt properties with a significant level of plasticity in terms of residual soil.